Synthesis of carbocyclic and 4'-disubstituted nucleoside analogs and progress towards the synthesis of bipyrimidine-bridged bis-dioxocyclams - Geisler, Lisa K., author; Hegedus, Louis S., advisor; Fisher, Ellen R., committee member; Kennan, Alan J., committee member; Finke, Richard G., committee member; Inamine, Julia M., committee member (Colorado State University. Libraries, 2002)
(-)-5-Benzyloxymethyl-5-ethoxy-5H-furan-2-one has been synthesized using chromium carbene chemistry; this versatile nucleoside template was then used for the total synthesis of (+)-neplanocin A. This synthesis showcased the development of a new reaction, a one-pot ring opening, intramolecular Wadsworth-Emmon reaction and was the first total synthesis of (+)-neplanocin A. During the synthesis insight was gained in the stereoselectivity of the cis-dihydroxylation of 5-benzyloxymethyl-5-ethoxy-5H-furan-2-one. Benzyloxymethyl-5-ethoxy-5H-furan-2-one was also utilized in the de novo synthesis a series of 4'-disubstituted nucleoside analogs. The 4'-ethoxy-dideoxyand 4'-ethoxy-dideoxydidehydronucleoside analogs were synthesized in good overall yield. Studies were performed on the synthesis of 4'-ethoxythymidine and 4'-ethoxy-2'-deoxythymidine to give the correct stereochemistry at the 2'- and 3'-positions. However, the desired diol could not be formed selectively. Synthesis of "unnatural" 2',3'-α-OH diastereomers was examined but the synthesis was hindered by the instability of the intermediates during formation of the glycosidic bond. Chromium carbene chemistry was also used to synthesize novel 5,12-dioxocyclams and studies were performed on the synthesis of bipyrimidine-bridged bis-dioxocyclams. The tetrakis(bromomethyl)bipyrimidine bridge was synthesized. Attempts were made to synthesize bipyrimidine-bridged bisdioxocyclams; however, the reaction was hindered by low yields or purification problems.
Keywords: organic chemistry